2023
DOI: 10.1002/jsfa.12589
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing quality traits of boiled yam: texture and taste for enhanced breeding efficiency and impact

Abstract: BACKGROUND: Boiled yam key quality attributes typical for West African consumers are: crumbly, easy to break, and sweet taste. New yam varieties are being developed but high or medium throughput tools to assess the required quality traits and their range of acceptance are limited. This study assessed the acceptance thresholds of these quality attributes and established the predictive models for screening yam varieties that meet the required consumers' preferences. RESULTS:Overall liking was associated with swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…[18][19][20][21][22][23] It has been shown that in D. alata a good eating quality combines high DM and starch contents. 19,24 The decline in DM content in the boiled pulp as compared to the raw samples was also reported by Adinsi et al 17 and is probably due to water absorption. 16 Crude protein content varied from 63 to 94 g kg −1 , which is in good agreement with the range of 45-99 g kg −1 , 25 and 51-110 g kg −1 , 23 recorded in water yam in West Africa.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…[18][19][20][21][22][23] It has been shown that in D. alata a good eating quality combines high DM and starch contents. 19,24 The decline in DM content in the boiled pulp as compared to the raw samples was also reported by Adinsi et al 17 and is probably due to water absorption. 16 Crude protein content varied from 63 to 94 g kg −1 , which is in good agreement with the range of 45-99 g kg −1 , 25 and 51-110 g kg −1 , 23 recorded in water yam in West Africa.…”
Section: Discussionsupporting
confidence: 73%
“…Water absorption can be considered an indicator of chewiness ( r = 0.43). Similarly, Adinsi et al 17 . obtained a significant negative correlation between hardness determined using a texturometer and friability (crumbliness) assessed by sensory analyses ( r = −0.94) in boiled water and white yam.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Theoretically, hardness should increase with DM of RTB samples because water can plasticize the system. It is largely observed in pasty products, such as in pounded yam, 21 but positive correlations were only found between DM of raw samples and the hardness of boiled yam (as already reported 58,59 ) and fried (see Supporting information, Fig. S3) and boiled plantain.…”
Section: Impact Of Dry Matter Starch and Amylose On Cooking Propertiessupporting
confidence: 69%